Basic Forms of Compensation for Immaterial (Moral) Damage with Special Emphasis on Fear, Physical, Spiritual Pain According to the Legislation of the Republic of Kosovo - Dauti, Arta (Acta Universitatis Danubius. Juridica, 2022)
Besides the material damage, and notwithstanding it, moral damage can also be caused, the forms of which are increasingly becoming diverse. Monetary compensation for the immaterial (moral) damage is determined expressively in the positive law of the Republic of Kosovo. Injured party - the the victim can obtain monetary compensation for the immaterial damage, for the physical and spiritual pain, for the reduction of life activity, disfigurement, violation of authority and honor, violation of freedom or personality rights, death of a close person, and fear, whereby, if the court states that the circumstances, especially the intensity of suffering and fear and their duration justify this, it will judge the appropriate monetary compensation, regardless of the immaterial damage and the absence of material damage. The study on this paper is mainly focused on the national legislation, and its key subject is the immaterial (moral) damage compensation, as well as presenting the court decisions of the competent courts in Kosovo. Whether the compensation will be determined or not, depends on the intensity and duration of the suffering, for each specific case. Upon the decision on the claim for the compensation of immaterial damage, as well as for the amount of the compensation, the court shall consider the importance of the violation and the purpose to which this compensation shall serve in order not to support the tendencies that are not compatible with nature and the social purpose thereof.